The Participation of the Java Sumatra Archipelago Youth Association (PENJARA) in Preventing the Occurring of Corruption Crimes: Case Study of the Central Leadership Council of the Nusantara Java Sumatra Youth Association (PENJARA) - Satria Nanda; Nurhimmi Falahiyati; Sahbudi (Jurnal Smart Hukum (JSH), 2024)
The general purpose of this research is to find out how the implementation of the role of youth participation in the Java-Sumatra archipelago in upcaya prevention and eradication of criminal acts of corruption. To find out how the government's efforts to optimize the prevention and eradication of corruption in Indonesia. The research method is a way or effort to do something by using the mind carefully to achieve a goal by searching, writing, arranging, formulating and analyzing until preparing a report. empirical legal research is research or observation in the field or field research whose research is focused on collecting empirical data. The approach method used in this research is the juridical-empirical method. Juridical-empirical research is legal research regarding the enactment or implementation of normative legal provisions directly on every legal event that occurs. The government's efforts in preventing and eradicating corruption are very worrying and pose a threat to the government, including synchronizing legislation or regulatory arrangements, fostering human resources, and digitizing government in preventing and eradicating corruption. Synchronizing legislation or regulatory arrangements. Synchronizing legislation or regulatory arrangements, adjustments and alignments related to the law on the prevention and eradication of corruption. Human Resource Development (HR) Providing education to the public about the prevention and eradication of corruption in accordance with Article 13 of Law No.30 concerning the Corruption Eradication Commission is a paradigm in the prevention and eradication of corruption, as a key success factor in the prevention and eradication of corruption. Socializing the prevention and eradication of corruption program. Digitalization and technology efforts in Indonesia are so massive that it is necessary to meet the requirements if we want to encourage the digitalization of all public services as an effort to prevent and eradicate criminal acts of corruption.